El branding como generador de reconocimiento de la unidad educativa intercultural bilingüe Huayna Capac de la parroquia de San Pablo de la ciudad de Ambato - Punina Azogue, Luis Eduardo (2024)
The Huayna Capac Intercultural Bilingual Educational Unit is an educational institution located in the parish of San Pablo in the city of Ambato, dedicated to providing quality education based on the principles of interculturalism and bilingualism. The institution focuses on promoting cultural diversity and respect for native languages, providing its students with a comprehensive education that includes both academic development and the preservation of their cultural identity. The present research work arises from the need to strengthen the recognition of the Educational Unit in a highly competitive environment. Despite its efforts to offer a differentiated education, the institution faces challenges in terms of its visibility and public perception, which limits its ability to attract new students and consolidate its presence in the educational market. This study justifies the importance of developing effective branding that not only enhances the institution's image, but also reinforces its educational and cultural mission. The methodology employed in this research included conducting surveys and interviews with different stakeholders, such as students, parents and faculty. The analysis of these data revealed that, although the institution has a solid educational proposal, there are significant weaknesses in its communication and in the coherence of its visual identity. These findings were fundamental for the development of the branding strategies proposed in this project. As a result of this study, a branding proposal was designed that focuses on three key areas: strengthening the institutional brand, developing a coherent visual identity, and optimizing the use of social networks for communication and promotion of the institution. These strategies are aimed at improving the recognition of the Huayna Capac Intercultural Bilingual Educational Unit, ensuring that its educational and cultural proposal is perceived in a positive and attractive way by its target audience.